EFFECT OF CHLORAMBUCIL ALONE AND IN COMBINATION WITH ASCORBIC ACID ON GLUTATHIONE, GLUTATHIONE-RELATED ENZYMES, MUTAGENICITY AND HISTOPATHOLOGY IN TUMOR-BEARING MICE - S. KALITA; SURYA B. PRASAD (International Journal of Pharma and Bio Sciences, 2015)
Chlorambucil is an anticancer drug with alkylating and immunosuppressive properties. The present findings show that the combination treatment of tumor-bearing mice with ascorbic acid plus chlorambucil has much better therapeutic efficacy against murine ascites Daltons’ lymphoma in comparison to chlorambucil alone and this may involve a decrease in GSH in Dalton’s lymphoma tumor cells. Chlorambucil-induced chromosomal aberrations, sperm abnormalities and histopathological changes in liver, kidney and testes were decreased after combination treatment. The analysis of renal function test (RFT) and liver function test (LFT) also suggest an improvement in these parameters after combination treatment. The increased GSH level, changes in GSH-related enzymes in the tissues i.e. kidney, liver and testes after combination treatment may be involved in its protective ability against chlorambucil-induced toxicity in the host. The present studies demonstrate a protective role of ascorbic acid against chlorambucil-induced mutagenicity and tissue toxicity in the hosts.